Kajian keberkesanan sisa ekstrak patchouli (Pogostemon Cablin) terhadap kesan menghalau tikus sawah (Rattus Argentiventer) - Wan Norlinda Roshana, Mohd Nawi (2012)
Study on the usage of natural material such as essential oil from plants as new alternative to chemical insecticides and pesticides has been actively conducted by researchers. Patchouli essential oil is a new source of material that seems to be of potential to repel insects and pesticides. However, the issue of using extracted patchouli oil as insects and pesticides repellent seems to be costly and of low value return since patchouli oil is of high demand especially in fragrant, cosmeceutical and pharmaceutical industries. The present study was, hence, conducted to investigate the possibility of using patchouli extraction waste as agent for rat repellent. Initial study on the maximum content of patchouli oil in samples of Pogostemon cablin (a type of patchouli plant) via 4 hourly sequence of hydrodistillation yielded 2.5 % (weight/weight) oil after 24 hours extraction.Analysis via gas chromatography mass spectrometer (GCMS) revealed that patchouli alcohol is the main component of patchouli oil, with content ranges from 36.0% to 47.0 %. Hence, study on natural evaporation of patchouli oil via solid phase microextraction (SPME) was focused on the evaporation of patchouli alcohol to the surrounding. A quadratic regression model with correlation, R2 = 0.9818, represents the best fit for the natural evaporation of patchouli alcohol with respect to the exposure time. From preliminary study on the effect of patchouli oil on rats using a transparent horizontal cylindrical pvc tube gave rise to the development of the methodology in carrying out the study of the extraction waste as rat repellent. The effectiveness of patchouli oil in repelling the paddy field rats was monitored based on the location of rat in the experimental box and the behavioral activities it showed in response to the presence of patchouli alcohol in the atmosphere with respect to exposure time. Using 60 mg sample, which represents oil content in the extraction waste from the 5th 4 hourly extraction, and using the proposed quadratic model, it was found that after 30 minutes of exposure time, with estimation of PA content, 0.129 mg in the surrounding, the rats were effectively repelled from the oil-sample bait. It was also observed that after 50 minutes of exposure time, estimated releasing 0.238 mg patchouli alcohol (PA) to the surrounding showed behavioral effect to the exposed rats. The effectiveness of the patchouli oil on rats was related to the olfactory system it possesses. Hence, the study concluded that the waste from the pathouli extraction still contained sufficient patchouliessential oil is repellent to paddy field rats.